Aspidistra Production and Use - Robert H. Stamps (EDIS, 2003)
There are from eight to over thirty species of Aspidistra depending on which taxonomist is queried. At the current time, there are only a few species that are fairly readily available for sale and there is some controversy as to which species are which. Therefore, buyers should make sure that what they are ordering is what they want. This document is ENH890, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 4, 2003.